Should we aspire to screen preschool children for conduct disorder?. Issue 10 (26th April 2009) - Wilson, P; Minnis, H; Puckering, C; Gillberg, C
Abstract : Life-course persistent conduct disorder is a major public health problem with implications for individual health and for society at large. Recent evidence has shown that treatment can be cost-effective, and early symptom detection is improving. We weigh the evidence for and against the introduction of population screening for conduct disorder in early childhood using Wilson and Jungner's criteria.